EFFECT OF MOLYBDENUM CONCENTRATION AND SPRAYING STAGES ON SEED YIELD AND ITS COMPONENTS OF ALFALFA - Naseer F. Shachai; Rzan Z. A.AI-Beiruty; Hameed. KH. Khrbeet (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
A field experiment was carried out at the experimental field in the College of Agricultural Engineering Sciences, University of Baghdad, Iraq from beginning of October 2020 to the end of August 2021. The main objective was to find out the effect of Molybdenum (Mo) concentrations (0, 20, 40 and 60 mg L-1 ) and three stages of foliar application (vegetative growth, flowers buds appearance and 25 % blooming ) on seed yield and it’s component of alfalfa local variety. layout of the experiment was R. C. B. D. arranged in split-plot, with three replicates. Spraying stages were used as main-plots. while Molybdenum concentrations were used as sub-plots. Results revealed that foliar application of Mo at concentration More than 20 mg L-1 (40 and 60 mg L-1) resulted in a significant increment in the No. of florets raceeme-1, No. of pods raceme-1, No. of seeds pod-1, No. of racemes stem1, Biological yield, seed yield and harvest index. Highest seed yield (502.0 k ha1) was obtained when Mo sprayed at level 40 mg L-1.Plants sprayed at flowers buds emergence produces highest seed yield (492.6 k ha-1), No. of pods raceme-1, No of seed pod-1 and No. of racemes stem, which show high positive correlation with seed yield (+ 0.72**,+ 0.49** and +0.49*) respectively. This results may be indicating that these traits could be used as good selection criteria for breeding and improving seed yield in alfalfa. The higher seed yield (567.5 kg ha-1) was obtained when alfalfa plants were sprayed with Mo at concentration 40 mg L-1 in flowers buds emergence.